Heroin-Related Compartment Syndrome: An Increasing Problem for Acute Care Surgeons. Issue 9 (September 2017) - Benns, Matthew; Miller, Keith; Harbrecht, Brian; Bozeman, Matthew; Nash, Nicholas
Heroin use has been increasing in the United States with the rate of heroin overdose nearly quadrupling in the last 10 years. Heroin overdose can occasionally lead to compartment syndrome (CS) because of extended periods of immobility and pressure tissue injury. Heroin-related compartment syndrome (HRCS) has previously been described, but has been limited to isolated case reports. We sought to examine our experience with HRCS in the climate of rising rates of heroin use among the general population. Medical records of all patients undergoing operative decompression for a CS at our academic medical center over a six-year period (2010–2015) were examined. Patient demographics, operation performed, and etiology were recorded. Cases of HRCS were identified, and clinical outcomes examined. A total of 213 patients undergoing fasciotomy were identified. Twenty-two of these patients had HRCS. Heroin was the second most common etiology of CS after trauma. Only one case of HRCS presented during the first three years of the study period, with the remaining 95 per cent of cases occurring within the last three years. The most common single location for HRCSs was gluteal (31.8%); 36 per cent of HRCS patients needed dialysis and 27 per cent suffered complications such as tissue loss. The incidence of HRCS has increased dramatically over the past several years and is now the second most common etiology for CS in our patient population. Patients with HRCS may present with severe manifestations of CS and different body areas affected.